2020
DOI: 10.1088/1757-899x/815/1/012012
|View full text |Cite
|
Sign up to set email alerts
|

A Qualitative Study of the Wind Noise Cavity Inside of a Two Way Radio

Abstract: The cavity inside microphone of two-way radio can induced noise when involved in outdoor and windy condition. An investigation was performed in Viwika wind tunnel involving a flow visualizations techniques to clarify the flow noise behavior generated by the wind, particularly within the cavity. A smoke wire test was conducted using a cavity model at varying aspect ratio (L/D) between 0.7 and 3 in angle of attack of 0º with Reynolds number of 7831. A two-dimensional Computational Fluid Dynamic (CFD) models base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Hairudin et al [18] performed a wind tunnel test to investigate the effect of cavity position on noise levels, demonstrating that the farthest position resulted in minimal wind noise levels. In another study, Hairudin et al [19] used flow visualization method to examine the flow structure produced under different cavity length-to-depth (L/D) ratios of microphone ports through wind tunnel testing. The results indicated that microphone ports with a small L/D ratio produced a single vortex shedding, while those with larger L/D ratios exhibited multiple vortices.…”
Section: Introductionmentioning
confidence: 99%
“…Hairudin et al [18] performed a wind tunnel test to investigate the effect of cavity position on noise levels, demonstrating that the farthest position resulted in minimal wind noise levels. In another study, Hairudin et al [19] used flow visualization method to examine the flow structure produced under different cavity length-to-depth (L/D) ratios of microphone ports through wind tunnel testing. The results indicated that microphone ports with a small L/D ratio produced a single vortex shedding, while those with larger L/D ratios exhibited multiple vortices.…”
Section: Introductionmentioning
confidence: 99%